Novel approach to enhancing brain DHA uptake: the role of nannochloropsis microalgae extract - Ma, Kunpeng; Xie, Shuhui; Zhang, Ying; Liu, Haixiang; Yu, Wei; Chen, Peihua (Frontiers in Nutrition, 2025)
BackgroundDocosahexaenoic acid (DHA) plays a pivotal role in sustaining the normal function of the human brain and preventing metabolic and neurodegenerative disorders. Despite its significance, the bioavailability of DHA from current supplements is suboptimal due to the limited absorption capacity of the adult brain. Recent studies have highlighted the role of Mfsd2a transporter in facilitating brain DHA uptake when DHA is esterified to lyso-phosphatidylcholine (LPC).ObjectiveLyso-diacylglyceryltrimethylhomoserine (LDGTS), a betaine lipid that resembles LPC in structure and is abundant in Nannochloropsis microalgae oil, presents a promising method to enhance DHA absorption. This study aimed to examine whether LDGTS-containing microalgae oil can promote brain DHA uptake.MethodsSeven groups of mice were fed different lipid formulations alongside their regular diet. After 15 days, tissue and organ samples were collected for lipid extraction and fatty acid analysis. Brain DHA uptake was quantified and compared across groups.ResultsThe mice administered a combination of microalgae oil and triacylglycerol (TAG)-DHA showed a significant increase in brain DHA uptake compared to controls. This effect was not observed with TAG-DHA alone, microalgae oil alone, or krill oil. The facilitation of DHA incorporation was accompanied by a notable enhancement of pathways related to cell growth and retinol metabolism in the brain, while pathways associated with cellular apoptosis and inflammation were downregulated.ConclusionThese findings suggest that the inclusion of LDGTS-rich microalgae oil in DHA supplementation may offer a novel and effective strategy for improving the bioavailability of DHA in the brain.